2003
DOI: 10.1021/jf0340456
|View full text |Cite
|
Sign up to set email alerts
|

Alkylresorcinols in Cereals and Cereal Products

Abstract: The alkylresorcinol (AR) content of 8 commonly consumed cereals, 125 Triticum cultivars, milling fractions of wheat and rye, bread, and other cereal products was analyzed. ARs were found in wheat (489-1429 microgram/g), rye (720-761 microgram/g), triticale (439-647 microgram/g), and barley (42-51 microgram/g), but not in rice, oats, maize, sorghum, or millet. One durum wheat variety was found to have an exceptionally low level of ARs (54 microgram/g) compared to other durum wheat varieties (589-751 microgram/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
356
7
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(426 citation statements)
references
References 31 publications
57
356
7
6
Order By: Relevance
“…These values are comparable to literature: 61.9-65.5 mg/100 g FW by Ross et al (2003), 92.7 mg/100 g FW by Mattila et al (2005), 134.2 mg/100 g FW by Landberg et al (2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These values are comparable to literature: 61.9-65.5 mg/100 g FW by Ross et al (2003), 92.7 mg/100 g FW by Mattila et al (2005), 134.2 mg/100 g FW by Landberg et al (2009).…”
Section: Discussionsupporting
confidence: 88%
“…The alkyl chain in cereal ARs varies from 15 to 27 carbon atoms. They are located in the intermediate layers between pericarp and testa in the grain (Landberg et al, 2008), and are found in high concentrations only in whole grain and/or bran products of wheat (31.7-143.9 mg/100 g dry matter, DM) and rye (36.0-320.0 mg/100g DM), and in very small amounts in refined flour (white bread, most breakfast cereals, pasta) or in any other commonly consumed foods (Ross et al, 2003;Ross et al, 2004a;Ross and Kochhar, 2009;Annica et al, 2010). They are also present in triticale (43.9-64.7 mg/100 g DM), and in small amounts in barley (4.2-5.1 mg/100 g DM), but not in oats (Ross et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They are present in high amounts in rye, common-and durum wheat and in lower amounts in barley (Landberg et al, 2006a;Andersson et al, 2008). AR are located in the outer cuticule of testa or inner cuticule of pericarp and thus their occurrence in blood reflect individual intake of bran (Ross et al, 2001(Ross et al, , 2003Landberg et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…In rye, the quantitatively most abundant AR homologues are C17:0, C19:0 and C21:0, whereas C19:0 and C21:0 are the most abundant homologues in wheat (Ross et al, 2003). The ratio between C17:0 and C21:0 has been suggested to distinguish between different cereals because the ratio is close to 1.0 for rye, 0.1 for common wheat and 0.001 for durum wheat (Chen et al, 2004;Landberg et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Los alquilrescinoles son lípidos fenólicos presentes en las partes exter nas de ciertos cereales con propiedades antioxidantes y la posibilidad de tener efectos anticáncer y antimicrobiano (Ross et al, 2003). Los alquilrescinoles se encuentran en mayor cantidad en el centeno que en el trigo y casi nada en la avena y en el arroz.…”
Section: Alquilrescinolesunclassified